Analysis of the geometric concept system present in the teaching book of the 4th year of Fundamental Education - Ferreira, Merly Palma; Moraes, Silvia Pereira Gonzaga de (Educação Matemática Debate, 2021)
The objective of this text is to analyze of the geometric concept system present in the textbook Ápis of the 4th year of Fundamental Education. We question what the quality of teaching geometric concepts, present in the textbook, in the direction and formation of the student's mathematical thinking. For this analysis, we use the theoretical-methodological approach of Historical-Cultural Theory and Activity Theory under the framework of historical and dialectical materialism. We found that, in the teaching organization proposed by the textbook, the content worked on does not become the object of attention and study by the student, the tasks assume a technical and repetitive direction, focused on how to do and not why to do it, limiting the development of the school's mental operations, as they distance themselves from the object of study and its historical production process, they lead to unity with the system of geometric concepts.